BESARNYA GAYA YANG DIBUTUHKAN PISAU UNTUK MEMOTONG KARET PADA MESIN SHREDDER DI PT. XYZ - Sidabutar, Naqasya Asyrori; Darmadi, Herry; Simbolon, Bonar Wahyudi; Nelza, Novia; Simalango, Jeffri (universitas teuku umar, 2025)
Shredder machines are classified as cutting machines that use two types of rolls, namely feed rolls and shredder rolls. First the sheet will be inserted, then the feed roll will wrap around the rubber sheet which is pulled into the machine at the same time as the feed roll which wraps around the rubber sheet. Then the thread on the main roll plays the role of pulling the rubber sheet and also the solid corner of the main roll thread also acts as a knife which will press the rubber sheet together with the Death Knife which will clamp the rubber sheet until the rubber sheet is broken or cut. The events that occur in the process of cutting rubber sheets on the shredder machine are the occurrence of cutting forces between the interaction of angles on the main roll thread and also the death knife. This research uses observation and interview methods to collect this data. From the research results, it was concluded that the amount of cutting force required by the cutting knife to cut rubber into small pieces was 247,242 N. Meanwhile, the amount of power used to produce the cutting force to cut rubber sheets was 2,651 HP.